PEMAHAMAN PROFESI AUDITOR SYARIAH OLEH MAHASISWA AKUNTANSI DI UNIVERSITAS MATARAM - Bambang Bambang (Jurnal Riset Akuntansi, 2017)
This study is about the students' understanding of sharia audits with the aim to explore the understanding of the role of sharia auditors, the characteristics that must be owned by the Sharia auditor and the knowledge that must be owned. The paper uses quantitative approach of survey. Self-developed questionnaire are administered to respondents of the survey. The role of the auditor according to the students is expected in addition to provide an assessment of the fairness of the financial statements as well as conventional auditors also ensures Sharia financial compliance with sharia. This understanding revealed that student are not aware about the precise role of shari’ah auditors. Low confidentiality in characteristics may adversely affect the confidentiality of client information that affects the level of trust of the low sharia auditor. Sharia auditors need to also understand conventional finance in order to make the audit more effective. The paper highlights the practical imperative for the authorities to consider a holistic revamp of its education strategies in meeting future market demands for qualified and well trained shari’ah auditors. Universities need to seriously create linkages between university and with business developments and practices.